Analisis Manajemen Risiko pada UMKM “Hello Waffle Jatos Mall” - Lestari, Trie Ayu; Riskiawati, Suci; Kulsum, Reysa Siti (Universitas Serambi Mekkah, 2024)
MSMEs are micro, small and medium enterprises MSMEs can be a community choice for doing business in any field The city of Bandung includes various sectors such as food, drinks and others. The culinary sector is an option in Bandung City and in Bandung Regency. The application of risk management is important for MSMEs to prepare for uncertain conditions, this can lead to risks that should not be avoided but must be faced. For this reason, it is necessary to analyze risks using SWOT analysis which includes strengths, weaknesses, opportunities, threats. This research uses a qualitative research method, which is carried out by interviewing the Hello Waffle MSME players The risks faced by the owners of Hello Waffle MSMEs. The aim is to find out what risks are faced by MSMEs and identify strengths, weaknesses, opportunities and threats. SWOT analysis is also used to see the relationship between risk analysis and SWOT owned by Hello Waffle MSMEs. Increased rent and electricity costs, unstable cash flow management, fluctuations in raw material prices can disrupt production, damage to waffle making machines, high employee turnover. Competition due to the emergence of new competitors or similar businesses, lack of advertising facilities, uniqueness of the menu with many variations in the use of quality raw materials, affordable prices, strategic location, rental costs that are too high. social media platform unt.